Influence of Financial Leverage on Corporate Profitability: Does it Really Matter? - Daruwala, Zaheda (International Journal of Economics and Financial Issues, 2023)
Debt is an essential component of capital structure for firms. Companies use leverage to impact the returns that equity shareholders yearn for. In this study, the author attempts to establish a stochastic relationship between the use of leverage and the profitability of cement manufacturing firms worldwide primarily to assess whether leverage affects firm profitability. The study extends further to examine whether the level of debt affects the return on equity, return on assets and net profit margin in similar ways, as they are all proxies of profitability. The empirical analysis is performed on data from major cement companies listed on public exchanges worldwide. The data is collected from 2012 to 2018 with the sample size of the thirteen most prominent companies in the world in the cement manufacturing industry for seven years consisting of ninety-one observations. Panel data regression analysis using the fixed effect model is applied to the data to investigate the relationship between the variables. Firstly, the study finds that financial leverage has a statistically significant inverse impact on profitability within the cement industry worldwide. Secondly, the study expands to determine that not all profit measures are influenced in the same way. The variables of profitability that really matter include the return on assets indicating the profit measured relative to the efficient use of resources and net profit margin that measures the returns from sales and by minimizing costs. The study does not find similar outcomes in relation to return on equity which contradicts theories that support debt as adding value to shareholders. The theory posits the stance of the benefit of tax-deductibility of debt, leveraged to increase profitability, and this study illuminates the incongruity of practical experiences to that of theory. The results of this study would assist corporate decision-makers in their capital structure decisions to critically examine the level of the worthiness of the benefit of tax deductibility of debt contributing to the firm’s financial performance.